Tailoring shrimp aquafeed to tackle Acute Hepatopancreatic Necrosis Disease by inclusion of industry-friendly seaweed extracts - Félix, Rafael (2021)
Shrimp farming has been severely affected by Vibrio infections in southeastern Asia, with severe economic impacts. Invasive seaweeds are an increasing threat that can be strategically valorized by biotechnology, promoting economic development while contributing to ecologic remediation. Asparagopsis armata and Sargassum muticum are two such species that have been frequently reported as excellent bioactive compounds producers, namely anti-bacterial and antioxidant. Thus, A. armata and S. muticum were extracted in an industry-focused approach, using low amounts of ethanol and short extraction times at room temperature. Yield, in vitro antioxidant capacity by the 2,2-diphenyl−1-picrylhydrazyl radical scavenging assay, and in vitro antibacterial activity against Vibrio parahaemolyticus (microdilution) were optimized using Response Surface Methodology (RSM). Optimal extracts (one from each seaweed species) were incorporated in feed, and an in vivo trial using the whiteleg shrimp Penaeus vannamei was performed in industrial facilities using the supplemented feed (1.5, 3.5 and 7.5 g extract per kg feed). Feed quality (along an 8-week period under regular storage conditions) and shrimp performance (40-day trial) were studied, as well as post-challenge (infection by virulent Vibrio parahaemolyticus) mortality rate and hepatopancreas condition. The results from the RSM showed that lower extraction times and ethanol volumes maximized extracts' bioactive properties (A. armata – 20 min, 10 mL solvent per gram seaweed; S. muticum – 100 min, 10 mL.g−1). The seaweed extracts did not impact shrimp performance (no statistically significant differences in weight gain, feed conversion rate or survival). Asparagopsis armata selected extract at 7.5 g per kg feed was able to decrease feed contamination by fungi along time and reduce shrimp mortality by up to 50% upon challenge with V. parahaemolyticus. Despite lacking statistical significance, a difference in hepatopancreas condition after challenge could be identified in shrimp fed the supplemented feed.